2017
DOI: 10.1186/s12879-017-2354-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial prophylaxis outside the operating theatre, an audit in a university hospital

Abstract: Background: The prophylactic use of antimicrobial agents to prevent infections in non-surgical situations has hardly been investigated. We investigate the extent, indications and appropriateness of antimicrobial prophylaxis given outside the operating room in a tertiary care hospital. Methods: Four point-prevalence surveys were conducted in which all inpatients on that day were screened for the use of prophylactic antimicrobials: medical prophylaxis, prophylaxis around non-surgical interventions and surgical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…A previous report showed that about one-third of all antimicrobial prescriptions administered outside the operating rooms being prophylaxis, 21 which is consistent with the present data…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…A previous report showed that about one-third of all antimicrobial prescriptions administered outside the operating rooms being prophylaxis, 21 which is consistent with the present data…”
Section: Discussionsupporting
confidence: 93%
“…A previous report showed that about one‐third of all antimicrobial prescriptions administered outside the operating rooms being prophylaxis, which is consistent with the present data showing that the proportion of surgeries being performed in operating rooms was approximately 78%. The proportion of inappropriate antimicrobial prophylaxis use was 28.4% and the most common type of inappropriate use was prolonged administration, which is also consistent with previous reports . Therefore, we emphasise that revision of the clinical pathways successfully optimised this prolonged antibiotic use in both surgeries and non‐surgical invasive therapies.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations